Implementasi Quick Response Code Indonesian Standard (QRIS) sebagai Inovasi Sistem Pembayaran digital dalam Meningkatkan Efisiensi Transaksi pada Usaha Mikro Kecil dan Menengah - Ahmad Vajri Rahman; Nardiman Nardiman (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
The implementation of the Quick Response Code Indonesian Standard (QRIS) has become one of the strategic initiatives to accelerate the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) by promoting cashless transactions and improving financial management. This community service program aimed to enhance the knowledge, understanding, and practical skills of business owners in utilizing QRIS as a digital payment system at Cafe OPPA BOX, Padang City. The program employed a participatory approach consisting of several stages, namely initial observation to identify business needs, socialization on the benefits and mechanisms of QRIS, hands-on training, intensive mentoring during the implementation process, and evaluation of outcomes. Throughout the activities, participants were introduced to the registration process, transaction procedures, and strategies for integrating QRIS into daily business operations. The results demonstrated that the business owner successfully adopted and independently operated the QRIS payment system. The implementation contributed to faster, more practical, secure, and well-documented transactions while reducing dependence on cash payments. Furthermore, the program improved digital financial literacy, strengthened customer trust by providing more convenient payment options, and enhanced service quality. Overall, the adoption of QRIS supported the operational efficiency and competitiveness of Cafe OPPA BOX, illustrating the important role of digital payment systems in empowering MSMEs to adapt to the rapidly evolving digital economy.